1998
DOI: 10.1901/jaba.1998.31-447
|View full text |Cite
|
Sign up to set email alerts
|

Applying Behavior Analysis to Clinical Problems: Review and Analysis of Habit Reversal

Abstract: This article provides a review and analysis of habit reversal, a multicomponent procedure developed by Nunn (1973, 1974) for the treatment of nervous habits, tics, and stuttering. The article starts with a discussion of the behaviors treated with habit reversal, behavioral covariation among habits, and functional analysis and assessment of habits. Research on habit reversal and simplified versions of the procedure is then described. Next the article discusses the limitations of habit reversal and the evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
94
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 147 publications
(96 citation statements)
references
References 96 publications
1
94
0
1
Order By: Relevance
“…The theoretical concepts need to be concretely explained to allow the active involvement of the child in the therapeutic process, such as direct role playing and other activities. Treatment and therapeutic activities must not appear to the child as a task or a punishment for his/her behavior, but rather as a way to develop himself/herself and to feel better, and enhance his/her quality of life [85]. Generally speaking, psychotherapy, even if unstructured, can prove to be an appropriate solution to the syndrome's impacts, addressing low self-esteem, lack of social skills or incomprehension toward his/her symptoms [86].…”
Section: ▪ Psychosocial Interventions For Ticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical concepts need to be concretely explained to allow the active involvement of the child in the therapeutic process, such as direct role playing and other activities. Treatment and therapeutic activities must not appear to the child as a task or a punishment for his/her behavior, but rather as a way to develop himself/herself and to feel better, and enhance his/her quality of life [85]. Generally speaking, psychotherapy, even if unstructured, can prove to be an appropriate solution to the syndrome's impacts, addressing low self-esteem, lack of social skills or incomprehension toward his/her symptoms [86].…”
Section: ▪ Psychosocial Interventions For Ticsmentioning
confidence: 99%
“…This technique tends to increase self-esteem by giving a certain empowerment over their behavior. In order to determine the most efficient components of this model, some researchers have assessed abridged versions of HR [46,85,92,99]. The results show that awareness and training of an incompatible answer are the most significant elements for the effectiveness of a HR treatment from childhood to adulthood.…”
Section: Effectiveness Of Cognitive Behavioral Interventions ▪ Studiementioning
confidence: 99%
“…Habit Reversal Training (HRT) has become the treatment of choice for habit disorders such as tics, Tourette Syndrome, and trichotillomania (Miltenberger, Fuqua, & Woods, 1998). First developed by Azrin and Nunn (1973), this comprehensive treatment protocol is firmly based on behavioural analytic principles and includes the following components: awareness training, competing response training, self-monitoring, social support, and generalisation training (see details below).…”
Section: Treatmentmentioning
confidence: 99%
“…Recent literature reviews have suggested that the competing response (CR) component, in which a person learns to engage in a physically incompatible behavior contingent on the repetitive behavior or its antecedents, is primarily responsible for the efficacy of habit reversal (Miltenberger, Fuqua, & Woods, 1998). Although Azrin and Nunn (1973) originally proposed a 3-min duration for the CR, shorter durations have been effective (e.g., 1 min; Woods et al, 1999).…”
mentioning
confidence: 99%